Medium- to large-bodied mammals in the upper basin of the Barranca del Amatzinac, Hueyapan, Morelos, Mexico - Márquez Rivera, Miguel Abraham; Arellano, Elizabeth; Valenzuela-Galván, David; Cruz, Daryl D. (THERYA, 2026)
The Barranca del Amatzinac is the principal hydrological system in northeastern Morelos, crossing several municipalities, including the recently established Indigenous municipality of Hueyapan. Despite its ecological importance, reliable information on the diversity of medium- to large-bodied mammals—and other taxonomic groups—is lacking. Here, we present the first report on the diversity of medium- to large- bodied mammals and describe the activity patterns of species recorded in the upper basin of the Barranca del Amatzinac. We deployed 15 camera traps strategically across the upper basin and conducted 12 monthly sampling sessions from May 2023 to April 2024, each lasting one week. In parallel, we performed transect-based sign surveys (track and sign identification) with two walks per month over the same period. Species richness was estimated using Hill numbers. We also calculated proportional capture rates for each species recorded by camera trapping and encounter rates for each species recorded from signs and inferred activity patterns using the Diel.Niche package in R. In total, we documented 15 species of medium- to large-bodied mammals. With 1,183 trap-days, camera traps recorded 12 species, and nearly 264 km of transect walks yielded 11 species. Alpha diversity (α, using Hill numbers) was 6.57 for camera-trap records and 6.52 for sign surveys. The most common species were Dasypus mexicanus, Didelphis virginiana, and Bassariscus astutus. Consistent activity patterns were obtained for most of the photographed species, as well as seasonal changes in some taxa (Canis latrans and Nasua narica), suggesting temporal partitioning and responses to seasonal environmental variation. This study provides the first formal data on medium- to large-bodied mammals for the Indigenous municipality of Hueyapan and northeastern Morelos, establishing a baseline for future biological research in the area.